1972
DOI: 10.1037/h0033697
|View full text |Cite
|
Sign up to set email alerts
|

Role of visual imprinting in the emergence of specific filial attachments in ducklings.

Abstract: Suppression of newly hatched ducklings' distress vocalization by two distinctive stimuli was assessed before and after subjects were imprinted to one of them. Initially, both stimuli strongly suppressed distress calls. Later, only the stimulus involved in imprinting did so. The results suggested that the loss of control by the nonimprinted stimulus was age related and represented the development of fear to insufficiently familiar stimuli. In a second experiment, older ducklings were permitted lengthy exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…Many researchers (Baron & Kish, 1960;Bateson, 1964a;Boyd & Fabricius, 1965;Brown, 1975;Hoffman, Ratner, & Eiserer, 1972) have demonstrated that precocial birds can form DEVELOPMENT OF FILIAL ATTACHMENT 163 attachments to a novel moving object even if their initial exposure to the object occurs later than the 1st day posthatch (i.e., after the sensitive period). Experiment 3 sought to determine whether ducklings could also form an attachment to a conspicuous, but static, stimulus after the end of the sensitive period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers (Baron & Kish, 1960;Bateson, 1964a;Boyd & Fabricius, 1965;Brown, 1975;Hoffman, Ratner, & Eiserer, 1972) have demonstrated that precocial birds can form DEVELOPMENT OF FILIAL ATTACHMENT 163 attachments to a novel moving object even if their initial exposure to the object occurs later than the 1st day posthatch (i.e., after the sensitive period). Experiment 3 sought to determine whether ducklings could also form an attachment to a conspicuous, but static, stimulus after the end of the sensitive period.…”
Section: Discussionmentioning
confidence: 99%
“…Second, neither familiarity with a given static environment nor familiarity with a given moving stimulus is sufficient for newly hatched birds to begin to exhibit fear of novelty (i.e., presumably some amount of physiological maturation is also needed ;Hoffman & Ratner, 1973b). Third, precocial birds that are at least a few days old show the same sort of fear behavior (crouching, distress calls, flight) in response to novel static settings that they do in response to novel moving objects (Hoffman, Ratner, & Eiserer, 1972;Malcom & Graves, 1977;Salzen, 1962; Experiment 3 in the present series). Fourth, just as a fear stimulus will induce a young precocial bird to more strongly approach a familiar moving object (Sluckin & Salzen, 1961), SO too will it induce approach to a manipulable, but otherwise static, object with which a bird has been reared (Candland, Nagy, & Conklyn, 1963).…”
Section: General Conclusionmentioning
confidence: 99%
“…It is important to realize that visual-only exposure to an initially novel object is itself adequate to achieve strong behavioral control in older ducklings, provided that the duration of the exposure is sufficiently long (Bateson, 1964;Hoffman et al, 1972). Thus, in the present study, the slight suppression induced by the object that was presented only visually probably represented the earliest beginnings in the development of strong suppressive properties by that object.…”
Section: Methodsmentioning
confidence: 88%
“…Thus the work assessed the effects of tactile stimulation under conditions in which visual stimulation by itself would be relatively ineffectual in eliciting filial behavior (Hoffman, Ratner, & Eiserer, 1972). In doing so, the present study employed ducklings as subjects, in contrast to the imprinting research cited above.…”
mentioning
confidence: 90%
See 1 more Smart Citation